The Effect of 2,4 d on Multiplication Eksplan of Various Dragon Fruit (hylocereus sp) by In Vitro - Endah Wahyurini; Susilowati Susilowati (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2017)
Propagation of seedling by tissue culture technique is challenging step during cultivation of these plant. The addition of 2.4 D is very influential on multiplication plant on various varieties of dragon fruit. This research aimed to determine the interaction between varieties and 2.4 D for the multiplication of planlet, to determine the right varieties of plants and to determine the appropriate 2.4 D concentration yielding superior plantlet. The experiments were performed using Complete Random Design with two treatments and three replication. The first factor is varieties wich four ll evetreatments of red dragon fruit, super red, white and yellow. The second factor is 2,4 D which also consists of three level of treatment that is 2 mg / L, 3 mg / L and 4 mg / L. The results were analyzed using ANOVA with further Duncan Multiple Range Test at the level 5%. The results showed that the white of dragon fruit showed the longest shoot height, the use of 2.4 D did not affect the multiplication of dragon fruit eksplan, and the combination of white dragon fruit treatment with 2.4 D at 2 mg / L concentration gave a better influence in inducing growth of fresh weight of planlet, dry weight of planlet and antioxidant compound. While red dragon fruit with 2.4 D at concentration 3 mg / L give a better influence in inducing root length and root number.Keywords: 2,4 D, varieties of dragon fruit, in vitro.